PENGARUH BEBAN KERJA TERHADAP STRES KERJA DENGAN JENIS KELAMIN SEBAGAI MODERATOR PADA KARYAWAN - Mareta Ninda Ardilla; Idha Rahayuningsih (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2024)
Study examines gender as moderator of influence workload on work stress in employees at supermarkets x. A quantitative method was used with sample of 53 employees with non-probability sampling techniques. Data collection technique by distributing questionnaires as research instruments with workload scale and work stress scale. The data analysis technique uses multiple linear regression with hypothesis testing using moderation regression analysis. The results of study showed: 1) there was an effect of workload on work stress in employees at supermarkets x. The value of Rsquare coefficient is 0.645, which means a strong relationship between the influence of workload variables on work stress variable by 64.5% and remaining 35.5% influenced by other variables.; 2) Gender doesnt moderate the effect of workload on work stress in employees. This can be caused by things arent considered such as: number of samples that arent balanced between men and women, job characteristics, and working period.   Keyword : Workload, Work Stress, Gender and Moderation.